President Susilo receives PhD in Peace Leadership from UUM - New Sabah Times English, (KK) (New Sabah Times English (KK), 2012)
KUALA LUMPUR: Indonesian President Susilo Bambang Yudhoyono was yesterday conferred Honorary Doctor of Philosophy in Peace Leadership by Universiti Utara Malaysia (UUM).